Analysis of The Implementation of The Internal Control System Of Cash Expenditure in The Regional Financial and Revenue Management Agency of Pematangsiantar City - Saragih, Marintan; Tarigan, Vitryani; Nababan, Rina Tania (Program Studi Akuntansi Universitas Simalungun, 2025)
According to Government Regulation Number 60 of 2008, the Internal Control System is a process that is integrated into every action and activity of the organization, which is carried out continuously by the leadership and all employees. The aim is to provide adequate assurance of achieving organizational goals through effective and efficient implementation of activities, reliability of financial reporting, security of state assets, and compliance with laws and regulations. This study aims to determine how the implementation of the Internal Control System for Cash Disbursements is carried out at the Regional Revenue and Financial Management Agency of Pematangsiantar City. The method used in this study is a qualitative approach. The results of the study indicate that the implementation of the system has been running well and includes a number of internal control components in accordance with the provisions applicable to cash disbursement procedures